Avaliação hematológica de cães naturalmente infectados por Leishmania (Leishmania) chagasi submetidos a tratamento com antimoniato de meglumina - Ikeda-Garcia, Fabiana Augusta [UNESP]; Ciarlini, Paulo Cesar [UNESP]; Lopes, Raimundo Souza [UNESP]; Marques, Fábia Judice; Bomfim, Suely Rgina Mogami [UNESP]; Lima, Valéria Marçal Felix de [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Marcondes, Mary [UNESP] (My University, 2008)
The present research was carried out aiming to assess the hematological response of dogs with visceral leishmaniasis submitted to treatment. For this, seven animals naturally infected by Leishmania sp. were submitted to a treatment with 75 mg/kg meglumine antimoniate subcutaneously, 12-12h/3 weeks. In all animals, a complete blood count and bone marrow aspiration biopsy were carried out for a descriptive evaluation at up to seven moments: before the treatment, 30, 60, 90, 120, 150 and 180 days after the start of the treatment. Before the beginning of the experiment hematological alterations were observed in four of the seven dogs (57.1%), among them, nonregenerative anemia, lymphopenia, lymphocytosis and monocytosis. During the course of the experiment the occurrence of leukocytoses, such as left shift neutrophilia and eosinophilia, were observed in some of the animals. Before the beginning of the treatment (M1), the occurrence of erythrocytic hypoplasia was detected by bone marrow cytology in two of the dogs (28.6%). This was reversed through an increase in the amount of erythroid progenitor cells after the administration of meglumine antimoniate. Thus, it can be concluded that the treatment led to normalization of the hematological alterations and recovery of the bone marrow.
Hematological evaluation of dogs naturally infected by Leishmania (Leishmania) chagasi submitted to treatment with meglumine antimoniate
Keywords: Complete blood count; Dogs; Leishmania sp; Animalia; Canis familiaris; Leishmania donovani chagasi; Leishmania sp.